Is it worth issuing bonds in China? Evidence from stock market reactions - Paul-Olivier Klein; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
There has been a considerable expansion of corporate bond markets in China in the recent years. The objective of this study is to examine the stock market reaction following bond issuance by Chinese companies. In addition to analyzing for positive or negative reactions to bond issues, we consider the influences of ownership and management characteristics on the stock market reaction. Applying an event-study methodology to a sample of 481 bond issues of 347 Chinese companies over the period 2009–2013, the univariate results show that Chinese bond issues typically generate a positive stock market reaction. The reaction is only significantly positive, however, in the case of central state-owned companies (as opposed to those owned by local or provincial governments). The multivariate results indicate that insider ownership influences stock market reaction to a bond issue, while management characteristics have no discernable impact.
URN:NBN:fi:bof-201601071000
Keywords: G14; P34; 330